Migração e rendimentos no Brasil: análise dos fatores associados no período intercensitário 2000-2010 - Luiz Carlos Day Gama (2013)
Brazil passed in the last two decades trough deep economic changes, for periods of stagnation and economic growth that changed the agents economics decisions. This work investigates how these changes have affected the behavior of migrants, return migrants and non-migrants and their incomes. We use data from 2000 and 2010 Censuses. Amongst the main results we found that migrants and return migrants are positively selected, in both unobservable and observable characteristics. Being male, white, young, schooled and resident of rural area elevates the probability of migrate and return to hometown in 2000 and 2010. Migrants and return migrants are better remunerated than non-migrants. When the samples of men and women are compared we realize that discrimination based on race is more present between men than women. The feedback to formal education fell in the period for both women and men. When Migrants and return migrants are compared we note that while the decision to migrate seems be taken in rational way, the decision to return to their previous city is taken as a correction of a previous mistake. Finally, the conclusion is that the situation of workers improved in the last decade, given the growth of income, the drop in unemployment, increase in formal labor and decrease in income inequality, and migration appears to be connected with these changes, especially the last one.